OPTIMIZATION OF MAINTENANCE PERIOD FOR OIL AND GAS PRODUCTION EQUIPMENT WELLS IN TUBAN EAST JAVA FIELD USING MGR AND BERNARD’S APPROACHES - Yahya, Indra Nur; Darmadi, Djarot Bangun; Setiawan, Ari; Pratama, Rizki R (International Journal of Mechanical Engineering Technologies and Applications, 2024)
Mechanical failures can cause Electric Submersible Pump (ESP) disruptions, shortening their lifespan. Despite improvements in run-time, unexpected failures still result in significant production deferment and loss, especially for oil & gas production equipment in Tuban East Java (TEJ) field. Therefore, we used Reliability Centered Maintenance (RCM) to analyze FMEA, employing two methods: Montgomery and Runger's (MGR) and Bernard's approaches. The MGR approach provided a better prediction of the failure rate. The ESP flat cable has the highest RPN, requiring maintenance of US$59,342 for an ideal 509-day period.